The influence of Guanxi and knowledge of China's business environment on relationship initiation capabilities: The case of Australian SME service suppliers in China - Chan, Tysun (Curtin University, 2014)
The purpose of this research is to examine the influences guanxi resources, understanding of the Chinese business environment, environmental competition and salesperson effectiveness have on business relationship initiation capabilities with customers in the People’s Republic of China for Australian exporters. Thematic analysis is used to analyse qualitative survey data from 25 Australian small and medium enterprises (SMEs) supplying services to China. Quantitative responses from 72 firms are also examined via PLS based structural equation modelling.